2020
DOI: 10.1186/s12199-020-00901-5
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 change dietary habits and lifestyle behaviours in Kuwait: a community-based cross-sectional study

Abstract: Background The coronavirus pandemic has transformed and continues to transform and affect the daily lives of communities worldwide, particularly due to the lockdown restrictions. Therefore, this study was designed to understand the changes in dietary and lifestyle behaviours that are major determinants of health during the COVID-19 outbreak. Methods A cross-sectional study was conducted through an online questionnaire using a convenience sample of 415 adults living in Kuwait (age range 18–73 years). Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
176
5
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(218 citation statements)
references
References 32 publications
25
176
5
12
Order By: Relevance
“…In addition, it was also reported that fast food intake was reduced [ 19 ]. Another study confirmed a drastic decrease of fast-food frequency consumption during COVID-19, with up to 82% adults reporting no fast food consumption [ 18 ]. There was also a significant increase in the percentage of participants who home cooked their main meal, but without differences in consumption of fruit and vegetables [ 18 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, it was also reported that fast food intake was reduced [ 19 ]. Another study confirmed a drastic decrease of fast-food frequency consumption during COVID-19, with up to 82% adults reporting no fast food consumption [ 18 ]. There was also a significant increase in the percentage of participants who home cooked their main meal, but without differences in consumption of fruit and vegetables [ 18 ].…”
Section: Discussionmentioning
confidence: 88%
“…Another study confirmed a drastic decrease of fast-food frequency consumption during COVID-19, with up to 82% adults reporting no fast food consumption [ 18 ]. There was also a significant increase in the percentage of participants who home cooked their main meal, but without differences in consumption of fruit and vegetables [ 18 ]. We described a positive change in dietary pattern, with 20–38% of students recording an increased intake of fruit and vegetables during lockdown, nevertheless similar percentage of students reported an increased intake of sweets and snacks.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In China, Wang and colleagues found that 75% of 2289 individuals isolated at home rated their sleep as very good [ 11 ], but a smaller prospective study found that 37% of a sample of young Chinese adults reported a worsening of their sleep quality during the pandemic [ 12 ]. Studies conducted in other countries have demonstrated that lockdown could either lead to an increase in the amount of time spent in bed [ 13 , 14 ], with good sleep efficiency [ 13 ] or associated with sleep disorders [ 15 , 16 ] and disruption of one’s habitual circadian rhythm [ 14 ]. This topic has also been investigated in Europe, where 55% of Spanish adults changed their sleep pattern after the beginning of the lockdown [ 17 ], and individuals who were physically active prior to the SARS-CoV-2 spread reported major sleep problems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Di Renzo [ 8 ] found improved dietary habits during the COVID-19-induced restrictions: a sample of 3533 Italian participants aged 12–86 years, 76.1% of which were females, tended to adhere to the Mediterranean diet, especially those between 18 and 30 years of age, with an increased uptake of organic foods, including fruits and vegetables. According to a study conducted in Kuwait, in a sample of 415 participants aged 18–73 years, changes in eating practices could be reported, including reduced consumption of fast-food and junk food, and increased ingestion of fresh, healthy food, such as fish and seafood [ 9 ]. During confinement, people have greater access to food because they work and live in closer proximity to their homes and kitchens.…”
Section: Introductionmentioning
confidence: 99%